The roles and functions of private security companies in UN Peace Missions - a critical analysis - Feldman, Daniel (Department of Political Studies, 2018)
This master's thesis analyses the roles that private security companies (PSCs) assume during United Nations (UN) peace missions. Following a literary review and contextual development of the PSC industry, this thesis makes use of a qualitative desktop study to examine five UN peace mission case studies in Africa in which PSCs were contracted to provide multiple roles for the UN. The case studies include UNAVEM, UNAMSIL, UNMIL, UNAMID, and MONUSCO. Each case study features a historical overview of the country's conflict, the UN mandate-related developments prior to and during the UN peace mission, the roles performed by PSCs in the peace operation, as well as a critical analysis of such PSC involvement. A subsequent discussion on the UNs use of PSCs finds that contracting provides the organisation with cost savings, more efficient operational capabilities, and the evasion of domestic sensitivities with regards to member state involvement in peace missions. The use of contractors, however, does also highlight the UNs vetting deficiencies in terms of the use of illegitimate companies, procurement issues - especially favouritism and corruption, and grave accountability problems associated with criminal prosecution mechanisms and the use of force by PSCs in the field. The thesis concludes that the reliance on contractors impacts the UNs peace mission endeavours in terms of increased militarization, a neo-colonial facet, and a gradual move towards privatized peacekeeping.